No Saints around Here : A Caregiver's Days - Toth, Susan Allen (Book collections on Project MUSE., 2014)
When we promise "in sickness and in health," it may be a mercy that we don't know exactly what lies ahead. Forcing food on an increasingly recalcitrant spouse. Brushing his teeth. Watching someone you love more than ever slip away day by day. As her husband James's Parkinson's disease with eventual dementia began to progress, writer Susan Allen Toth decides she intensely wants to keep her husband at home-the home he designed and loved and lived in for a quarter century-until the end. No saint, as she often reminds the reader, Toth found solace in documenting her days as a caregiver. The result, written in brief, episodic bursts during the final eighteen months of James's life, has a rare and poignant immediacy. Wrenching, occasionally peevish, at times darkly funny, and always deeply felt, Toth's intimate, unsparing account reflects the realities of seeing a loved one out of life: the critical support of some friends and the disappearance of others; the elasticity of time, infinitely slow and yet in such short supply; the sheer physicality of James's decline and the author's own loneliness; the practical challenges-the right food, the right wheelchair, the right hospital bed-all intricately interlocking parts of the act of loving and caring for someone who in so many ways is fading away. "We all need someone to hear us," Toth says of the millions who devote their days to the care of a loved one. Her memoir is at once an eloquent expression of that need and an opening for others. No Saints around Here is the beginning of a conversation in which so many of us may someday find our voices.